WHIPPLE PROCEDURE: PANCREATICOGASTROSTOMY VERSUS PANCREATICOJEJUNOSTOMY: A LITERATURE REVIEW - Rehman, Sameer; Umer, Affan; Kuncewitch, Michael; Molmenti, Ernesto (Journal of Ayub Medical College Abbottabad, 2016)
Pancreatic cancer is one of the leading causes of oncologic morbidity and mortality worldwide. The definitive surgical management for pancreatic cancer includes pancreaticoduodenectomy with either anastomosis to, or implantation of remnant pancreas to the stomach (pancreaticogastrostomy) or the jejunum (pancreaticojejunostomy). Operative morbidity and mortality following pancreaticoduodenectomy frequently results from complications associated with a pancreaticojejunal anastomotic leak. Pancreaticogastrostomy is an alternative method of restoring pancreatic continuity with the gut, which has been employed by a number of institutions showing some benefit in operative mortality.